Adsorptive Separation of Acetylene from Ethylene in Isostructural Gallate‐Based Metal–Organic Frameworks. Issue 68 (31st October 2019) - Wang, Jiawei; Li, Liangying; Guo, Lidong; Zhao, Yingcai; Xie, Danyan; Zhang, Zhiguo; Yang, Qiwei; Yang, Yiwen; Bao, Zongbi; Ren, Qilong
Abstract: The separation of acetylene from ethylene is of paramount importance in the purification of chemical feedstocks for industrial manufacturing. Herein, an isostructural series of gallate‐based metal–organic frameworks (MOFs), M‐gallate (M=Ni, Mg, Co), featuring three‐dimensionally interconnected zigzag channels, the aperture size of which can be finely tuned within 0.3 Å by metal replacement. Controlling the aperture size of M‐gallate materials slightly from 3.69 down to 3.47 Å could result in a dramatic enhancement of C2 H2 /C2 H4 separation performance. As the smallest radius among the studied metal ions, Ni‐gallate exhibits the best C2 H2 /C2 H4 adsorption separation performance owing to the strongest confinement effect, ranking after the state‐of‐the‐art UTSA‐200a with a C2 H4 productivity of 85.6 mol L −1 from 1:99 C2 H2 /C2 H4 mixture. The isostructural gallate‐based MOFs, readily synthesized from inexpensive gallic acid, are demonstrated to be a new top‐performing porous material for highly efficient adsorption of C2 H2 from C2 H4 . Abstract : Removing acetylene from ethylene : Isostructural gallate‐based metal–organic frameworks (MOFs) are demonstrated to be a new family of top‐performing porous materials for highly efficient separation of acetylene from ethylene (see figure).